The Responsible Inclusion of Students Receiving Special Education Services for Emotional Disturbance: Unraveling the Practice to Research Gap. Issue 4 (July 2019) - McKenna, John William; Solis, Michael; Brigham, Frederick; Adamson, Reesha
The majority of students receiving special education services for emotional disturbance (ED) receive a significant amount of instruction in general education classrooms, which emphasizes curriculums based on college and career readiness standards. In turn, those teachers who provide instruction to students with ED in inclusive settings are responsible for using evidence-based practices (EBPs) for those teaching situations in which they exist to meet free appropriate public education (FAPE) mandates. However, the identification of EBPs is a necessary pre-condition to eventual school adoption and teacher use of such practices. In this investigation, we completed a synthesis of syntheses to (a) determine the degree to which academic intervention research has focused on students with ED in general education classrooms and (b) identify practices that are effective at improving the academic performance of students with ED in these settings. Overall, few studies were identified. Of those studies identified, half did not disaggregate outcomes for students with ED. A quality indicator coding based on the What Works Clearinghouse (WWC) design standards revealed that no studies with disaggregated outcomes permitted causal inferences. Implications for school practice and areas for future research are discussed.